Covering Up Chelmno: Nazi Attempts to Obfuscate and Obliterate an Extermination Camp. Issue 3 (2nd September 2018) - Terry, Nicholas
ABSTRACT: The centrality of deception and secrecy to the Nazi extermination of the Jews has long been recognized, yet numerous questions remain regarding its significance for the Final Solution. This article examines Nazi attempts to cover up the first extermination camp established by the Third Reich at Chelmno. It demonstrates that in the Warthegau region of occupied Poland, the Nazis played a shell game to deceive victims and bystanders by pretending that deportees were transferred from the provinces to the Lodz ghetto or from the Lodz ghetto to the provinces and Germany. The contradictory cover stories used by the Nazis to obfuscate deportations to Chelmno succeeded for a while, but were eventually seen through. While Nazi deception measures are more vividly recorded in postwar testimonies, this article also shows that Nazi attempts to erase the physical evidence of mass murder through the cremation of the corpses can be documented much more extensively than hitherto appreciated using contemporary sources. Ultimately, both the attempted obfuscation and obliteration of the evidence for extermination at Chelmno failed.